2009
DOI: 10.1186/1471-2407-9-80
|View full text |Cite
|
Sign up to set email alerts
|

ADAM33 gene silencing by promoter hypermethylation as a molecular marker in breast invasive lobular carcinoma

Abstract: BackgroundADAM33 protein is a member of the family of transmembrane glycoproteins composed of multidomains. ADAM family members have different activities, such as proteolysis and adhesion, making them good candidates to mediate the extracellular matrix remodelling and changes in cellular adhesion that characterise certain pathologies and cancer development. It was reported that one family member, ADAM23, is down-regulated by promoter hypermethylation. This seems to correlate with tumour progression and metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 27 publications
4
27
0
Order By: Relevance
“…All the IDC samples were ADAM33 protein positive in IHC. However, 11 out of 38 tumoral samples (Table 1) showed to be hypermethylated in the ADAM33 promoter as seen in our previous work [13]. This result could be explained by other epigenetic mechanisms involved in the silencing of this gene as discussed below.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…All the IDC samples were ADAM33 protein positive in IHC. However, 11 out of 38 tumoral samples (Table 1) showed to be hypermethylated in the ADAM33 promoter as seen in our previous work [13]. This result could be explained by other epigenetic mechanisms involved in the silencing of this gene as discussed below.…”
Section: Resultsmentioning
confidence: 64%
“…The results showed that mouse sera have high specificity for ADAM33 recombinant protein since no signal was detected in the MDA-MB-231 cell line, which does not express the ADAM33 gene [13] (Figure 2). Moreover, MCF7 and PMC42 cell lines that express the ADAM33 gene showed a single and strong signal of approximately 37 kDa for this protein.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations